1995
DOI: 10.1046/j.1471-4159.1995.65031348.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Glutamatergic Pathway from the Guinea Pig Auditory Cortex to the Inferior Colliculus

Abstract: We attempt to provide evidence that the projection from the guinea pig auditory cortex (AC) to the inferior colliculus (IC) may contain glutamatergic or GABAergic fibers. Seven days after unilateral AC aspiration, histological studies indicated almost complete AC destruction and preterminal degeneration of fibers and terminal fields in the dorsal cortex (DCIC), external cortex (ECIC), and central nucleus (CNIC) of the IC ipsilateral to the ablated AC. Contralaterally, degeneration appeared in the DCIC. AC abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 52 publications
9
92
0
2
Order By: Relevance
“…The shortest latency responses to cortical stimulation (1.0 -1.4 msec) were always excitatory, and the authors concluded they were probably monosynaptic. This is consistent with work suggesting that the corticocollicular axons use glutamate as a neurotransmitter (Feliciano and Potashner 1995). Longer latency responses (1.8 -4.2 msec) included excitatory and inhibitory effects, and are likely to include di-or multisynaptic circuits.…”
Section: Cortical Effects On Ic Cellssupporting
confidence: 87%
“…The shortest latency responses to cortical stimulation (1.0 -1.4 msec) were always excitatory, and the authors concluded they were probably monosynaptic. This is consistent with work suggesting that the corticocollicular axons use glutamate as a neurotransmitter (Feliciano and Potashner 1995). Longer latency responses (1.8 -4.2 msec) included excitatory and inhibitory effects, and are likely to include di-or multisynaptic circuits.…”
Section: Cortical Effects On Ic Cellssupporting
confidence: 87%
“…Previous data support the role of glutamate as the main excitatory neurotransmitter in the inferior colliculus (Faingold, 2002;Caicedo and Eybalin, 1999;Feliciano and Potashner, 1995;Gaza and Ribak, 1997;Goldsmith et al, 1995;Helfert et al, 1999;Liao et al, 2000;Moore et al, 1998;Parks, 2000;Saint Marie, 1996;Suneja et al, 1995Suneja et al, , 2000. In addition, glutamine and glutamate have numerous functions in different organs working as precursors for neurotransmitters, related proteins, nucleotides, nucleic acids and glutathione synthesis.…”
Section: Introductionmentioning
confidence: 68%
“…In some of the responses, antidromic spike activity was also observed. Anatomical studies (Feliciano and Potashner 1995;Winer 2005;Winer et al 1998) showed that monosynaptic corticofugal projections exist from A1 to ICC and that electrical stimulation within ICC can antidromically activate cortical neurons originating from layer V (Mitani and Shimokouchi 1985). Although we attempted to position our recording sites in layer IV of A1, it is possible that some of our responses were contaminated with antidromic spike activity recorded from layer V. There is also evidence, at least for projections from the visual cortex to the superior colliculus, that antidromically activated dendritic processes extending from corticotectal cells located in layer V can elicit spike activity in layers III and IV of the cortex (Schofield et al 1987).…”
Section: Discussionmentioning
confidence: 99%